Liberdade de consciência na obra O Grande Conflito de Ellen G White - Santos, Tiago Cesar (2016)
This research aims to deepen the understanding of freedom of conscience in the thinking of Ellen G. White, focusing especially on the reflections contained in one of his works, The Great Controversy. Therefore this research describes the social, historical and religious lived by the author pointing out the main factors that influenced his life. Then we seek to understand what the relationship of her writings to the Bible, analyzing its hermeneutics. In the final part there is a description of the history of the work's composition, followed by an analysis of it, seeking to assess the impact that your thoughts have brought their time and still reflect today. Although Ellen G. White is not a theoretical renowned and considering its limitations and its little academic training their reflections produced a religious ethos in the name of which he was co-founder of the Seventh-day Adventists, who encouraged them to be very active in the defense these principles. Through this research it was found that continued operation is the result of a vision that integrates the theme of freedom of conscience not only a historical dimension, but also eschatological